2021
DOI: 10.1111/cid.12983
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the effect of the size of lateral‐antrostomy in graftless balloon elevation of the maxillary sinus membrane with simultaneous implant placement (a randomized controlled clinical trial)

Abstract: Background The overlying maxillary sinus frequently restrains the height of the posterior maxillary bones. Purpose Evaluating the effect of downsizing the antrostomy side‐window on the stability of the installed implants and vertical bone gain, after employing a graftless antral membrane balloon elevation (AMBE). Materials and methods The study is a randomized controlled clinical trial conducted on 20 patients with 30 deficient maxillary alveolar ridges underwent graftless (AMBE) after being allocated into a (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In the current application of LSFE, a common procedure for preparing the accessing window is to directly grind the lateral wall bone using the rotary diamond round bur, but the remaining lateral defect is reported to have an adverse effect on endo-sinus bone healing (Yu & Qiu, 2017). In addition, current studies have shown that a smaller lateral window contributes to the early bone formation compared with a larger window whether undergoing grafting or not (Aldahouk et al, 2021;Zhu et al, 2021), which confirms the role of the lateral bone wall in endo-sinus bone augmentation. Besides, the residual lateral defect caused by the round bur would lead to the compensation of graft material to fill the lateral antrostomy hole, which might affect the endo-sinus augmentation effect of LSFE (Zhou et al, 2021; Figure 1a).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In the current application of LSFE, a common procedure for preparing the accessing window is to directly grind the lateral wall bone using the rotary diamond round bur, but the remaining lateral defect is reported to have an adverse effect on endo-sinus bone healing (Yu & Qiu, 2017). In addition, current studies have shown that a smaller lateral window contributes to the early bone formation compared with a larger window whether undergoing grafting or not (Aldahouk et al, 2021;Zhu et al, 2021), which confirms the role of the lateral bone wall in endo-sinus bone augmentation. Besides, the residual lateral defect caused by the round bur would lead to the compensation of graft material to fill the lateral antrostomy hole, which might affect the endo-sinus augmentation effect of LSFE (Zhou et al, 2021; Figure 1a).…”
Section: Introductionsupporting
confidence: 69%
“…A recent histomorphometric study in rabbits found that repositioning of the bone window could accelerate endo-sinus bone generation and generate more new bone (31.28 ± 3.51% vs. 21.74 ± 2.40%; p < .05) and mature bone (27.37 ± 5.45% vs. 13.02 ± 3.69%; p < .05) at 8 weeks compared with the collagen membrane-covered group (Moon et al, 2014), proving the osteoinductive efficacy of the lateral wall bone. Other studies assessing the effect of the size of lateral wall antrostomy on endosinus bone formation also confirmed the above conclusion that lateral wall bone had a role of osteoinduction and acted as the source of osteogenesis, providing growth factors and a blood supply for bone regeneration (Aldahouk et al, 2021;Avila-Ortiz et al, 2012;Yu & Qiu, 2017;Zhu et al, 2021). The above studies were in agreement with the results in this study, demonstrating that the repositioned bone wall would be beneficial to the graft stability, especially to the region near the bone window.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Lately, cone-beam computed tomography (CBCT) has been considered as a promising three-dimensional (3D) option in evaluating the extent of peri-implant bone augmentation surrounding the implant 14,23,27,30 . However, 3D analysis of the grafted area of lSFE with a small window and minimally invasive techniques for lSFE are scant and have short follow-up periods 14,30,31 . In the consistence of these studies, authors veri ed that the stability of implants and excellent osteogenic capacities were detected 6 months after small antrostomy surgery.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the periimplant bone augmentation, various imaging approaches have been utilized 29 . Lately, cone-beam computed tomography (CBCT) has been considered as a promising three-dimensional (3D) option in evaluating the extent of peri-implant bone augmentation surrounding the implant 14,23,27,30 . However, 3D analysis of the grafted area of lSFE with a small window and minimally invasive techniques for lSFE are scant and have short follow-up periods 14,30,31 .…”
Section: Introductionmentioning
confidence: 99%